Fall Risk Based on Timed Up and Go Test in Elderly at Nursing Home in West Java, Indonesia - Selvadurai, Thiruchelvam; Prabowo, Tertianto; Pratiwi, Yuni S. (Althea Medical Journal, 2017)
Background: Falls are major cause of morbidity and mortality in elderly patients. Mobility assessment is important in preventingÂ  falls in elderly. This study was conducted to determine the level of fall risk in elderly people at Karitas Cimahi Nursing Home, West Java, Indonesia by using âtimed up and go testâ(TUG).Methods:This cross-sectional descriptive study was conducted at Karitas Cimahi Nursing Home from JuneâNovember 2013. The risk of falls was categorized into two; high and low risk of falls. High risk of falls indicated when the participants complete the TUG test with time taken >10 seconds, and low risk of falls indicated when the time taken is <10 seconds. To identify the level of fall risk in elderly people the test which is recommended by the American Geriatric Society was used. The sampling technique used was total sampling. Data was analyzed and presented by using frequency tables.Results: From a total of 32 elderly population at Karitas Cimahi Nursing Home, a total of 20 participated in this study. The âTimed up and go testâ result for all the participants were >10 seconds. Conclusions: The level of fall risk in elderly people at Karitas Cimahi Nursing Home based on theÂ  test showedÂ  that all participants,Â  both male and female, regardless of using assistive device have high level risk of falls. [AMJ.2017;4(1):83â6]Â DOI:Â 10.15850/amj.v4n1.1025